EVALUASI FORMATIF DESAIN INSTRUKSIONAL DIKLAT JARAK JAUH PENELITIAN TINDAKAN KELAS - Asip Suryadi (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2020)
Classroom Action Research Online Training is one of Online Training (Diklat Jarak Jauh) organized by Jakarta Religion Training Office (BDK Jakarta). The training still has some weaknesses including low graduation rate and academic learning outcomes. It needs evaluation to formulate some revision in its instructional system. One of the important component should be evaluated is instructional design. This study explains formative evaluation results of the instructional design. The study was conducted to answer three questions, 1) Is the teaching material in accordance with the participants' wishes? 2). Is teaching material presented using the right strategy so that it is easy to learn? 3). Has the tutor service met the expectations of participants? The results of the study are expected to formulate recommendations for revision. Formative evaluations are conducted within the framework of Dick and Carey's instructional development model focuses on field trials level. The data was collected through surveys using ELL, activity logs, tutor records and recordings of participant’s conversations on social media. Survey results are processed using descriptive statistics and qualitative data processed using content analysis. The research concluded that teaching materials and teaching strategies are low scored. Based on the conclusion, it is recommended to change the structure curriculum to ensure that the teaching materials are more detailed, implement more diverse learning strategies and apply Web 3.0 as a base to determine media in accordance with the learning style of the digital community.